2005
DOI: 10.22621/cfn.v119i4.193
|View full text |Cite
|
Sign up to set email alerts
|

Water-bears from the Rocky Mountains: A First Look at Alberta's Tardigrade Fauna

Abstract: There is no information in the published literature regarding Alberta’s terrestrial water-bear (Tardigrada) fauna. We surveyed across an elevational gradient (1100 – 1800 ft) on Black Cat Mountain in the Alberta Rocky Mountain range. Ten taxa were identified from 902 specimens, all of which are new records for Alberta and one species is new for Canada: Macrobiotus cf. islandicus Richters, 1904. There was no clear relationship between elevation and tardigrade distribution, possibly owing to patchiness of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…and one was Hylocomium splendens ((Hedw.) Schimp), which are both common feather mosses in forested habitats and wooded peatlands and have relatively high tardigrade densities (Boeckner and Proctor, 2004;Jönsson, 2003) (Table 1). After collection, we stored samples in sealable plastic bags of 1 liter volume that was filled entirely with moss.…”
Section: Methodsmentioning
confidence: 99%
“…and one was Hylocomium splendens ((Hedw.) Schimp), which are both common feather mosses in forested habitats and wooded peatlands and have relatively high tardigrade densities (Boeckner and Proctor, 2004;Jönsson, 2003) (Table 1). After collection, we stored samples in sealable plastic bags of 1 liter volume that was filled entirely with moss.…”
Section: Methodsmentioning
confidence: 99%
“…Nelson (1982) updated Marcus (1939) for aquatic and semi-aquatic species, while McFatter et al (2007) reviewed North American freshwater Tardigrada. Rossi & Claps (1991) and Claps et al (2008) reviewed the tardigrades of Argentina, Assunção (1999) listed the tardigrade species of the state of São Paulo in Brazil, Boeckner et al (2005) provided a list of species found in Canada, Nickel et al (2001) summarized the tardigrades only weak support for such associations. On the other hand, Mitchell et al (2009) found significant evidence for both positive and negative associations between substrates and tardigrade species.…”
Section: Introductionmentioning
confidence: 99%